Insolvência das operadoras de planos de saúde brasileiras: uma análise empírica do efeito de fatores internos e externos à firma - Bastos, Larissa Lenotti Zuliani Nogueira (2019)
This study aims to investigate the level of compliance of health care providers and how the characteristics (internal and external) of the providers affect the probability of noncompliance with the limits imposed by the National Agency for Supplementary Health (ANS). The theory of public finances and the theory of the economy regulation were used as theoretical basis, and the economic-financial data were extracted from the ANS’s web pages and refer to the period from 2007 to 2017. Based on the descriptive statistics, the findings showed that there are more solvent companies than insolvent but with a significant increase in the number of insolvent companies. The logistic regression models showed that variables such as age and size are negatively related to the increase in the insolvency probability of the operators. On the other hand, factors such as modality and geographic coverage give rise to greater chances of insolvency. Moreover, in low-concentration sectors, medium- and small-sized carriers are more prone to insolvency.